Customer satisfaction and customer retention as a result of e-Service quality after the COVID-19 breakdown. Issue 5 (4th July 2022) - Fathima, Ifra; Radhika, R.; Fathima, A.
Abstract: With various technological innovation and digital payment system, customer expectations for the banking services has raised and these changes have paved a way for superior customer quality and satisfaction. The present study has utilized e-servqual modified model and format to evaluate the banking service satisfaction and retentions. The online survey has been distributed and collected among 167 people in Chennai city using a non-probability sampling technique. Furthermore the present study employed SPSS software to evaluate the banking service quality and satisfaction among the potential customers. As a result of e-servqual quality dimensions a positive association has been identified among potential retained customers.